Developing Scenarios for Exploring Teacher Agency in Universities: A Multimethod Study - Kusters, Max; De Vetten, Arjen; Admiraal, Wilfried; Van der Rijst, Roeland (Frontline Learning Research, 2024)
Lecturers who are actively engaged in shaping their teaching and teaching practices demonstrate agency. Teacher agency has increasingly been described as a key factor in educational development at universities. Lecturers are expected to innovatively develop courses and continuously improve their teaching practices to respond to, for example, student needs and labor market demands. In this multimethod study, we examined the process of developing and validating scenarios for measuring teacher agency in universities. We conducted four studies to create 23 scenarios that capture the complex nature of teacher agency. First, we interviewed university lecturers to identify bumpy moments in their teaching practice, and so found scenarios based on real-life experiences. Then, we employed two expert panels, to evaluate and refine the scenarios, which enhanced their validity. Finally, we used a pilot study to standardize the data collection procedures. Our multimethod study has established reliability by triangulating methods and researchers, involving multiple stakeholders, and providing detailed descriptions of the research process. This project holds implications for research and practice. The scenarios can be used in professional academic development programs for the collection of research data and to promote self-reflection, peer consultation activities, and professional growth and agency among university lecturers.